Heat exchanger design based on earthen materials. (15th July 2021) - Bouchenna, Chafea; Huchet, Florian; Aramiou, Carl; Hamard, Erwan; Le Guen, Laurédan; Paul, Jean-Marc
Abstract: We propose herein the design of a heat exchanger based on clay materials in order to reduce the energy consumed due to data center cooling. Our Thermal Energy Storage (TES) system is to be placed upstream of the CRAC (Computer Room Air Conditioner) unit. A direct contact heat exchanger is thereby built as a vertical packed bed, composed of earthen spheres whose imposed heating/cooling cycles comply with ASHRAE (American Society of Heating, Refrigerating and Air-Conditioning Engineers) standards. A raw earthen material has been chosen owing to its hygrothermal characteristics, which are recognized as relevant for indoor thermal regulation, in addition to a low embodied energy required for manufacturing. Results show that the pore Reynolds number and sphere diameter exert significant effects on the energy buffering capacity. A simple relationship is thus proposed to link the mass-specific power of the energy storage system, the internal heat exchanger architecture and the pore Reynolds number for purposes of designing raw earth bricks at an elevated scale.